Factors Affecting Talent Management on Organizational Performance: Evidence from Kathmandu Valley - Shakya, Somi; Siddique, Majibur Rahman; Poudel, Devi Kumari (International Research Journal of MMC, 2026)
Background: Human Resource Management has evolved into a strategic function that enhances organizational performance through effective talent management. In competitive and dynamic environments, talent has become a critical asset. In the present time, organizations face talent shortages, mismatches, and retention challenges, yet empirical evidence on how talent management practices influence organizational performance remains limited. Purpose: This study aims to examine the impact of talent management practices on private sector organizational performance within Kathmandu Valley. It further seeks to identify key challenges faced by such organizations and propose practical managerial solutions to improve talent management. Design/methodology/approach: The study adopted both descriptive and explanatory research designs. Social Exchange Theory underpins the research, as it explains the reciprocal relationship between employers and employees in enhancing productivity. The study was conducted in the Kathmandu Valley. Data were collected using non-probability convenience sampling from 403 respondents through structured questionnaires. KOBO Toolbox, Excel, and SmartPLS 4 were used for data management and analysis. Both descriptive and inferential statistical analyses were employed. Findings: The findings reveal that knowledge management, reward management, and training and development have significant positive effects on organizational performance, whereas personal attributes show no significant influence. The study further indicates that 94.54% of respondents perceive the existence of talent management challenges within their organizations, with biased evaluation practices being the most frequently reported issue (59.06%). To address these challenges, respondents emphasized several improvement measures, particularly the need to foster a supportive and positive working environment (54.59%). Conclusion: In conclusion, the study confirms that effective talent management practices significantly enhance organizational performance in private sector of Kathmandu Valley.